Food, Eating Practices and Identity in Postcolonial Hong Kong: A Study of Cha Chaan Tengs, Soy Sauce Western Cuisine and the Narrative of Indigenisation - Wang, Yimo (Auckland University of Technology, 2026)
Food is closely linked to human history, and often acknowledged as a symbol of a region or nation’s culture. The culinary history of a cuisine helps people understand the cultural identity of the region or group. In societies shaped by colonial histories, political changes, and cultural shifts, familiar food acts as a vital collective memory and provides a sense of belonging for many locals. Accordingly, people’s daily food practices can reflect their tastes, dietary choices, and rules of eating, and can be used to examine how a group’s food practices contribute to understanding their food culture by connecting the past and present, affirming “who they are” and why they are different from other groups. Hong Kong is a world-famous city that was under British colonial rule for over a hundred years and has been influenced by Western culture for a long time. Following the return of sovereignty to China in 1997, localist culture and China’s communist culture have been in ongoing conflict, with debates surrounding political instability and local identity continuing. In recent years, an increasing number of democratic movements have prompted Hong Kong’s people to reflect on their culture, identity, and sense of belonging. This dissertation investigates the role of food in shaping identity through the case of Hong Kong people’s food practices in cha chaan tengs and their soy sauce Western cuisine. Because cha chaan tengs and their cuisine developed through colonial influence and local adaptation, they occupy an ambiguous cultural position between traditional Chinese and Western culture. This makes it an ideal lens for exploring the development of local culture and the formation of identity in a postcolonial context. The study examines people’s food practices through the lens of social orders, communal functions, and shared memories, focusing on culinary hybridity, dining behaviours, and nostalgic narratives of cha chaan tengs. It explores how characteristics of hybridity in culinary practices manifest in people’s everyday food practices, and how the culture of cha chaan tengs is regarded as a distinct culture that reflects diners’ behaviours and norms, distinguishing insiders from outsiders. Additionally, the study investigates how nostalgic narratives of cha chaan tengs transmit local culture and reinforce the cultural heritage of food. The cha chaan tengs and their soy sauce Western cuisine are chosen as a case study subject because the role of food in the expression and construction of identity highlights the importance of examining ordinary cultural forms to understand broader social processes. The study demonstrates the dynamics of identity production beyond individual self-expression and reveals that identity is not a fixed cultural essence. Additionally, the study offers a valuable perspective on how local culture operates through daily life, providing a framework that may be applied to other postcolonial and culturally hybrid societies.